Psychosocial problems and childhood recurrent abdominal pain - Orawan Louthrenoo (2018)
Objective: Recurrent abdominal pain (RAP) is a challenging problem in general pediatrics. The present study aimed to assess psychosocial problems associated with children with RAP. Material and Method: Children aged 5-15 years with symptoms of abdominal pain for more than 3 months, interfering with their daily life and activities and control children were consecutively enrolled. Psychosocial assessment was obtained by using a semi-structured interview and the Pediatric Symptom Checklist (PSC). Complete physical examination, basic investigations, and esophagogastroduodenoscopy was performed in children with RAP. Results: Forty-two children with RAP and 45 controls were enrolled into the study. With age and family demographically controlled, psychosocial problems and the PSC scores in children with RAP were not significantly different from those in controls. Psychosocial problems related to RAP could be the primary etiology in some cases, but may be consequent or coexist. Conclusion: The findings in the study suggest a biopsychosocial approach in children with RAP. Psychosocial assessment should be considered even in RAP with identified organic findings.